93.0k views
3 votes
Please help I’m confused!

Please help I’m confused!-example-1

2 Answers

5 votes

Answer:

2nd option;
c=9-a+b

Explanation:

  1. The first thing you need to do, is rewrite the equation without the square root.
  2. So for instance
    √(16)=4 and
    16=(4)^2 therefore
    a-b+c=(3)^2
  3. Then
    a-b+c=9
  4. Now we take away '
    a ' on both sides and add '
    b ' on both sides
  5. So
    a-(a)-b+(b)+c=9-(a)+(b)
  6. Which gives us
    0+0+c=9-a+b which is simply
    c=9-a+b

Hope this helps

User Chadlagore
by
4.8k points
2 votes
Number 2 is the answer););!;!:!;!;!;!;!;!;!;!;!;?;
User Remees M Syde
by
5.7k points